2010
DOI: 10.1158/1078-0432.ccr-10-1092
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Polycythemia Vera Identifies Gene Expression Patterns Both Dependent and Independent from the Action of JAK2V617F

Abstract: Purpose: To understand the changes in gene expression in polycythemia vera (PV) progenitor cells and their relationship to JAK2V617F.Experimental Design: Messenger RNA isolated from CD34 + cells from nine PV patients and normal controls was profiled using Affymetrix arrays. Gene expression change mediated by JAK2V617F was determined by profiling CD34 + cells transduced with the kinase and by analysis of leukemia cell lines harboring JAK2V617F, treated with an inhibitor.Results: A PV expression signature was en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…This is consistent with a role for these miRNAs in erythropoiesis, which is the principal feature of PV. This is not surprising as PV CD34+ cells have been shown to be more lineage-committed than the normal CD34+ cells [50,51]. Our data provide the first microRNA basis for this lineage preference of PV hematopoietic stem/progenitor cells.…”
Section: Discussionsupporting
confidence: 58%
“…This is consistent with a role for these miRNAs in erythropoiesis, which is the principal feature of PV. This is not surprising as PV CD34+ cells have been shown to be more lineage-committed than the normal CD34+ cells [50,51]. Our data provide the first microRNA basis for this lineage preference of PV hematopoietic stem/progenitor cells.…”
Section: Discussionsupporting
confidence: 58%
“…The extent to which JAK2 V617F contributed to gene expression remains undefined, but no significant differences in gene expression were observed in a study of CD34+ bone marrow cells from JAK2 V617F–positive and JAK2 V617F–negative patients with polycythemia vera. 3 In our study, the JAK2 V617F allele burdens did not differ between the group with aggressive disease and the group with indolent disease, even though their gene-expression patterns differed overall (Tables S5A and S5B in the Supplementary Appendix) and with respect to the set of 102 core genes (Table S6A and S6B in the Supplementary Appendix), suggesting an important role of other signaling pathways in the pathogenesis of poly-cythemia vera.…”
Section: Discussionmentioning
confidence: 43%
“…2 Several lines of evidence suggest that additional genetic and epi-genetic factors are involved. For example, in poly-cythemia vera and essential thrombocytosis, gene expression in CD34+ bone marrow cells does not differ between JAK2 V617F–positive and JAK2 V617F–negative patients, 3,4 and clonal granulocytes in patients with polycythemia vera do not always express JAK2 V617F. 5 Furthermore, JAK2 V617F expression, regardless of the allele burden, has been shown not to influence signal transduction in circulating CD34+ cells in patients with poly-cythemia vera.…”
mentioning
confidence: 99%
“…Given the known relationship between expression of CDX2 and induction of KLF4 in colonic epithelial cells, through additional, as yet unknown mechanisms. Another recent study identified downregulation of KLF4 as a consequence of the JAK2 V617F mutation in polycythemia vera (PV) (58). This observation may point to a more general role for reduced KLF4 activity in myeloid leukemogenesis; however, the functional significance of KLF4 repression in PV remains to be determined.…”
Section: Discussionmentioning
confidence: 99%